Analysis of the Corruption Case of Social Assistance Funds During the Covid-19 Pandemic In the Perspective of Government Ethics - Sri Wulan Ningsih; Rachmat Ramdani (Peneliti.net, 2022)
Based on Law Number 31 of 1999, corruption is the act of any person who unlawfully commits an act of enriching himself or another person or a corporation that can harm the country's finances or the country's economy. Corruption is also defined as the action of any person with the aim of benefiting himself or another person or a corporation. Corruption cases are now more focused on prevention rather than prosecution. The reason is that the actions that have been carried out so far are considered to only have a shocking effect and have not minimized corruption. The public is also waiting for the strategy and effectiveness of preventing corruption. The same thing happened in the Bansos corruption case in 2020. This article contains an analysis of the corruption case in the perspective of government ethics using qualitative research methods and descriptive research types.